The clean energy revolution tipping point is inevitable—but the sooner, the better - Arndt, Channing (2017)
As global leaders gather for the UN’s annual COP meetings on mitigating the impacts of climate change, an energy revolution is underway with enormous implications, not least for the world’s poor. Renewable energy adoption will be a crucial component of meeting the Paris Climate Agreement to hold a rise in global temperatures below two degrees Celsius, and market forces are accelerating those adoption rates. Perhaps as important as the impact this could have on our environment though, is the promise it holds for improving conditions and development prospects in the developing world.